Mouse embryonic palatal mesenchymal cells maintain stemness through the PTEN-Akt-mTOR autophagic pathway - Shi, Lungang (Stem Cell Res Ther, 2019)
BACKGROUND: Both genetic and environmental factors are implicated in the pathogenesis of cleft palate. However, the molecular and cellular mechanisms that regulate the development of palatal shelves, which are composed of mesenchymal cells, have not yet been fully elucidated. This study aimed to determine the stemness and multilineage differentiation potential of mouse embryonic palatal mesenchyme (MEPM) cells in palatal shelves and to explore the underlying regulatory mechanism associated with cleft palate formation. METHODS: Palatal shelves excised from mice models were cultured in vitro to ascertain whether MEPM are stem cells through immunofluorescence and flow cytometry. The osteogenic, adipogenic, and chondrogenic differentiation potential of MEPM cells were also determined to characterize MEPM stemness. In addition, the role of the PTEN-Akt-mTOR autophagic pathway was investigated using quantitative RT-PCR, Western blotting, and transmission electron microscopy. RESULTS: MEPM cells in culture exhibited cell surface marker expression profiles similar to that of mouse bone marrow stem cells and exhibited positive staining for vimentin (mesodermal marker), nestin (ectodermal marker), PDGFRα, Efnb1, Osr2, and Meox2 (MEPM cells markers). In addition, exposure to PDGFA stimulated chemotaxis of MEPM cells. MEPM cells exhibited stronger potential for osteogenic differentiation as compared to that for adipogenic and chondrogenic differentiation. Undifferentiated MEPM cells displayed a high concentration of autophagosomes, which disappeared after differentiation (at passage four), indicating the involvement of PTEN-Akt-mTOR signaling. CONCLUSIONS: Our findings suggest that MEPM cells are ectomesenchymal stem cells with a strong osteogenic differentiation potential and that maintenance of their stemness via PTEN/AKT/mTOR autophagic signaling prevents cleft palate development.